ANALISIS PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP PENDAPATAN PENGUSAHA - Sukmajati (STIE Swasta Mandiri Surakarta), Amru (Manajemen Bisnis Syariah, 2011)
Jobs that become more difficult nowadays causing socioeconomic problemfor the people. The increase in unemployment will cause a burden to the governmentand of course disrupt stability of the socioeconomic. Higher education does notguarantee a person becomes easy to get a job moreover the majority people ofIndonesia are poorly educated. One solution to overcome this problem is MicroSmall and Medium Enterprise (UMKM). In many countries, UMKM provedcapable of providing jobs. Many factor can affect the success of the UMKMenterpreneurs, which are often judged by the level of income. This research willexplore socioeconomic factors that can effect any income level of the UMKMenterpreneurs. In subsequent research will be discussed how to manage UMKM sothat this enterprise can be run by anyone and may alleviate unemployment.Keywords: Micro Small and Medium Enterprise (UMKM), socioeconomic